2017
DOI: 10.1108/maj-02-2016-1319
|View full text |Cite
|
Sign up to set email alerts
|

Gender in accounting research: a review

Abstract: Purpose This paper aims to review studies dealing with gender issues in accounting literature over the period of 1994-2016. Design/methodology/approach This study combines electronic and manual searches to identify relevant studies using keywords such as “gender” or “female” and “earnings quality” or “social and environmental disclosure” or “auditing” or “tax aggressiveness”. In total, 64 published studies were identified. Findings Three main streams of gender accounting literature related to financial rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
23

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 95 publications
5
64
1
23
Order By: Relevance
“…The result of this study is consistent with prior literature (e.g. Lai et al, 2017 ;Khlif & Achek, 2017;Hardies et al, 2015;Huang et al, 2014).…”
Section: Multivariate Regression Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The result of this study is consistent with prior literature (e.g. Lai et al, 2017 ;Khlif & Achek, 2017;Hardies et al, 2015;Huang et al, 2014).…”
Section: Multivariate Regression Resultssupporting
confidence: 93%
“…Hardies et al, (2015) studied Belgian firms and concluded higher audit fees for female audit engagement partners. Likewise, Khlif & Achek (2017) studies dealing with gender issues in accounting literature over the period of 1994-2016 and found findings shows that female representation on the board, audit committee, CFO or CEO leads to higher audit fees along with more conservative reporting, higher level of social and environmental disclosure, less tax aggressiveness. In line with the above literature, it is argued that as female members are more cautious about the firm's performance and ethical issues, they tend to ensure higher audit quality given by specialist external auditors and thus audit fees increase.…”
Section: Female Members Representation In Boardmentioning
confidence: 97%
“…However, despite the strategic importance of CSR to many organisations, very few studies have addressed the question of the role played by the CEO in the dissemination of information on CSR [46,47]. Previous studies have been based mainly on characteristics like age, see for example [48]; experience and tenure, see for example [46,49]; and gender, see for example [49,50] as decisive regarding CSR, but none have analysed their disclosure via social media.…”
Section: Upper Echelons Theorymentioning
confidence: 99%
“…With regard to the organization's disclosure of social and environmental information, empirical studies have shown that when the company board has a higher proportion of female members, there tends to be more corporate transparency [50].…”
Section: Upper Echelons Theorymentioning
confidence: 99%
“…The introduction in the 1960s of a number of gender-focused equal opportunities laws, especially in developed countries, such as the 1963 Equal Pay Act of the US, helped in increasing women's participation in the workforce (Khlif and Achek 2017). However, this did not necessarily lead to increased participation of women in senior management roles [e.g., board member or chief executive officer (CEO)] in companies, with 'old-boys networks' often cited as one of the major barriers to women's executive career progression (Adams 2016).…”
Section: Introductionmentioning
confidence: 99%